2015
DOI: 10.1007/s00784-015-1504-6
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of fit and efficiency of CAD/CAM fabricated all-ceramic restorations based on direct and indirect digitalization: a double-blinded, randomized clinical trial

Abstract: The results show that a direct, intraoral, digitalized impression technique is more accurate and efficient when compared with conventional impressions in fabricating single crowns and three-unit FDPs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
120
1
10

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(150 citation statements)
references
References 46 publications
8
120
1
10
Order By: Relevance
“…Furthermore, patients' satisfaction with digital impressions was significantly higher than with conventional impressions [20]. Although both direct and indirect digitalization facilitates the fabrication of single crowns and three-unit FDPs with clinically acceptable marginal fit.…”
Section: Discussionmentioning
confidence: 92%
“…Furthermore, patients' satisfaction with digital impressions was significantly higher than with conventional impressions [20]. Although both direct and indirect digitalization facilitates the fabrication of single crowns and three-unit FDPs with clinically acceptable marginal fit.…”
Section: Discussionmentioning
confidence: 92%
“…However, accuracy, which represents trueness, is difficult to evaluate in vivo because the real dimensions of the test participant, the gold standard (ISO 5725–1) [27,28], cannot be easily measured in the oral cavity of patients. Therefore, in vivo evaluations of accuracy are often performed by measuring the fit of final restorations [3,7,20,29,30]. Studies have reported clinically acceptable fit of restorations fabricated using a digital impression technique and when compared to restorations fabricated using conventional impressions [6,3134].…”
Section: Discussionmentioning
confidence: 99%
“…7 A recent in vitro trial evaluated the difficulty level and the operator's perception of 30 dental students and 30 experienced clinicians when making digital and conventional implant impressions. 12 The difficulty level of optical impressions was similar between the student and the clinician groups.…”
Section: Discussionmentioning
confidence: 99%
“…6 It was concluded that the digital pathway may shorten the duration of the overall clinical treatment and technical production process achieving a beneficial cost-benefit ratio. Another clinical study comparing the time efficiency of digital and conventional impressions for the fabrication of tooth-supported restorations 7 found that the quadrant optical impressions are significantly less time consuming than complete-arch conventional impressions.…”
Section: Introductionmentioning
confidence: 99%